Implementasi Kebijakan Parkir Berlangganan di Kabupaten Sidoarjo (Studi Di Dinas Perhubungan Kabupaten Sidoarjo) - Siti Fatimah; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2018)
This study aims to analyze and describe the implementation of a subscription parking policy in Sidoarjo Regency as well as supporting and inhibiting the implementation of a subscription parking policy in Sidoarjo Regency. The type of this research is descrip- tive research with qualitative approach. Data collection is done by observation, interviews, and documentation with informants. Data analysis technique uses Miles & Huber- man theory, namely data collection, data reduction, data presentation, and conclusion. The results showed that the implementation of a subscription parking policy in Sidoarjo Regency had not run effectively because the standard operating procedures had not been implemented optimally by the supervisors and carved out a subscription; facilities and infrastructure are inadequate; as well as the salary of supervisors and parking atten- dants subscribers are minimal. The conclusion of this study is that the implementation of a subscription parking policy in Sidoarjo Regency has not run effectively related to stan- dard operating procedures, facilities and infrastructure, and the level of compliance of the parking attendants subscription.